Potential Inhibition of Filamentous Microorganisms in Sludge Bulking by Static Magnetic Field - Syamimi Zaidi, Nur; Muda, Khalida; Hussein, Norelyza; Sillanpää, Mika (International Journal of Engineering and Technology, 2018)
In activated sludge system, the performance of the process largely depends on the balance between filamentous and floc-forming microorganisms. When the normal balance of these biological communities is disturbed, filamentous microorganisms tend to proliferate, causing various problems to the treatment performances such as sludge bulking. Various approaches have been used to control the proliferation of filamentous microorganisms. However, the approaches led to various drawbacks that eventually worsen the performances of treatment systems. Therefore, this study is aimed to investigate the potential approach using static magnetic field in inhibiting filamentous microorganisms that presence in the sludge bulking. Magnetic field of intensity 88 mT was used. Its exposure on the filamentous microorganisms was investigated in terms of filaments’ characteristics such as branching, shape and filaments’ location. The analysis indicated that the magnetically exposed activated sludge showed less possibility presence of the filamentous microorganisms compared to unexposed activated sludge. Â Â